The diversification benefits of investing in Bitcoin - Dias, José Manuel Barroso Martins Salgado (2022)
In this dissertation we aim to study the diversification benefits of investing in Bitcoin in a context of a well-diversified, balanced portfolio constituted by bonds and stocks (classic 60% equity/40% bonds Traditional Portfolio). Based on historical data, we evaluate the impact of different (i) holding periods of the investment, (ii) rebalancing frequencies of the portfolio and (iii) range of bitcoin allocations, on the overall performance of a given portfolio. A rolling analysis was performed to capture the time-dependent dynamics between these assets. We conclude that, for the sample period under analysis, quarterly rebalanced bitcoin allocations between 0.5%-7.5% for a minimum holding period of 3 years have always been beneficial for the investor, regardless of the period in which the investment was made. Although past performance is no guarantee of future performance, we believe that the empirical conclusions presented in this dissertation have significant implications for institutional investors.